2020
DOI: 10.1177/2325967120947725
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Characteristics of Tissues Attached to the Fifth Metatarsal Bone

Abstract: Background: Two types of stress, bending stress and traction stress, have been reported to be involved in the mechanism of Jones fracture. However, little is known about the risk factors for traction stress. Purpose: To classify the attachment position of the peroneus brevis muscle (PB), peroneus tertius (PT), lateral band of the plantar aponeurosis (LB), and the long plantar ligament (LPL), focusing on the zone where a Jones fracture occurs (zone 2), and to compare the footprint area of each tissue type. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Kavanagh et al in a force platform analysis demonstrated that a vertical or medial lateral force is often required for a fracture to occur (13). Inversion injuries are responsible for tuberosity avulsion fractures (14), where peroneus brevis is already contracted during stance phase and has the potential of pulling the tuberosity fragment when the plantarly flexed foot is subjected to an inversion stress; the firm attachment of the lateral band of plantar aponeurosis, on the other hand, is implicated for fractures distally to the tuberosity (15, 16,17,18). Furthermore, Gu used a three-dimensional model to study stress loads on the metatarsals during landing, reporting that one of the peak stress points was in the proximal fifth metatarsal.…”
Section: Biomechanics and Predisposing Factorsmentioning
confidence: 99%
“…Kavanagh et al in a force platform analysis demonstrated that a vertical or medial lateral force is often required for a fracture to occur (13). Inversion injuries are responsible for tuberosity avulsion fractures (14), where peroneus brevis is already contracted during stance phase and has the potential of pulling the tuberosity fragment when the plantarly flexed foot is subjected to an inversion stress; the firm attachment of the lateral band of plantar aponeurosis, on the other hand, is implicated for fractures distally to the tuberosity (15, 16,17,18). Furthermore, Gu used a three-dimensional model to study stress loads on the metatarsals during landing, reporting that one of the peak stress points was in the proximal fifth metatarsal.…”
Section: Biomechanics and Predisposing Factorsmentioning
confidence: 99%
“…In addition, for the anatomical study, the lateral band of the plantar fascia and peroneus brevis are attached to the dorsolateral aspect of the fifth metatarsal base. Since the attachment point of the peroneus tertius is farther away from the fifth metatarsal base and the peroneus tertius has less strength than the other two tendons [ 16 ], we propose that the peroneus tertius does not play a major role in the avulsion fracture of the fifth metatarsal base. Following this, separate heat maps were generated for the fracture lines in the three zones that appeared most frequently on the overall heat map.…”
Section: Discussionmentioning
confidence: 99%
“…The fifth metatarsal bone base is involved in 30% of metatarsal fractures due to the anatomy and biomechanics of the pes quintus (fifth foot) [ 1 ]. The tuberositas ossis metatarsi quinti, which is a projection on the lateral surface of the fifth metatarsal bone and serves as an insertion point for ligaments and tendons [ 2 ], is highly prominent and increases the lever arm of the bone, leading to greater stress in this area [ 3 ]. Avulsion fractures of the tuberosity are frequent and caused by the sudden inversion and plantar flexion of the foot [ 4 ].…”
Section: Introductionmentioning
confidence: 99%